Mechanisms of Interaction of Subjects in the field of Preventing and Combating Domestic Violence at The Regional and Local Level - Korol, Natalia (Theory and Practice of Public Administration, 2022)
Violence against women and girls is not limited to any culture, region, country, or specific group of women. It happens in times of peace and war. The EU and its Member States have long demonstrated a commitment to eradicating violence against women by creating policies and contributing to international treaties that work towards this goal. Preventing and combating violence against women is a precondition for equitable and inclusive sustainable development. Violence against women, including domestic violence, cannot be considered simply a violation of women’s human rights, because it has a direct impact on the entire society.Co-ordinated measures and multi-agency partnerships are necessary to address the root causes of these problems. Interventions tackling violence against women and domestic violence need to be concentrated on the needs and the rights of the victims, and multi-agency co-operation is crucial in effectively preventing domestic violence against women and their children.